The Development of Teaching Material of In Vitro Plant Breeding Based on Scientific Literacy - Harahap, Fauziyah; Salsabila, Az-Zahra Shakila (Bioedukasi: Jurnal Pendidikan Biologi, 2022)
This development research was carried out based on the observations of lecturers and students Department of Biology at Universitas Negeri Medan who stated that the tissue culture course was still quite difficult to learn, and the level of scientific literacy in Indonesia according to PISA was still relatively low. So, the purpose of this development research in general is to improve student scientific literacy, one of which is by developing tissue culture teaching materials. The research method for developing tissue culture teaching materials refers to the Dick & Carey model. However, this research has only reached the stage of designing and conducting formative evaluation. Analysis of the data used in this development research using quantitative descriptive data analysis. The result showed that the development of teaching material of in vitro plant breeding based on scientific literacy with a feasibility level based on material expert validation obtained a percentage of 91% in the very worthy category, learning design expert validation obtained a percentage of 95% in the very worthy category, layout design expert validation obtained a percentage of 99,2% in the very worthy category, response from lecturer of tissue culture course obtained a percentage of 95% in the very worthy category, and student responses obtained a percentage of 87% in the worthy category.